(untitled) (Balneo and PRM Research Journal, 2022)
Scoliosis is defined as a three-dimensional deformity of the spine that is of particular interest to the lateral curvature of the spine. Various types of treatment approaches have been recommended for patients with scoliosis. The aim of this study was to provide an up-to-date review of scoliosis, focusing on issues such as its incidence and treatment methods. The ISI-Thomson Web Of Science International Virtual Library was accessed for this review. The search criteria selected were ’title’, ’abstract’ and ’keywords’. In the ISI Thomson Web of Science virtual library platforms, the keywords in the articles search were "scoliosis incidence" and "scoliosis treatment". Over the years, different therapeutic strategies have been addressed for patients with scoliosis, they differ depending on the type of scoliosis, the patient’s age and the available therapeutic means.